«Aplegar» i «arribar» en el «Curial e Güelfa»: un parell sinonímic? - Montserrat, Sandra (Caplletra. Revista Internacional de Filologia, 2008)
In this brief study we will carefully analyze the uses of arribar and aplegar in mediaeval language from Curial e Güelfa. Our goal is to discover when and up to which extent both verbs, arribar and aplegar, share their meaning during the first half of the 15th century, in order to shed light on the current situation of Valencian. At the same time, we will contrast the datum of this anonymous text with former, later and contemporary works from the datum of Corpus Informatitzat del Català Antic (CICA: 2007).